2012
DOI: 10.1029/2012ja017648
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of SC‐associated geosynchronous magnetic field perturbations

Abstract: [1] Kokubun (1983) reported the local time variation of normalized amplitude of sudden commencement (SC) with a strong day-night asymmetry (i.e., maximum amplitude near noon and minimum amplitude near midnight) at geosynchronous orbit with 81 SC events. Further careful inspection of Kokubun's local time distribution reveals that the normalized SC amplitudes in the prenoon sector (MLT = 9-12) are larger than those in the postnoon sector (MLT = 12-15). That is, there is a morning-afternoon asymmetry in the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 29 publications
5
25
0
Order By: Relevance
“…This distribution characteristic is consistent with results from Park et al []. The reason for this kind of distribution is suggested to be related to dawn‐dusk asymmetric response to enhancement of solar wind dynamics [ Park et al , , ].…”
Section: Summary and Discussionsupporting
confidence: 91%
“…This distribution characteristic is consistent with results from Park et al []. The reason for this kind of distribution is suggested to be related to dawn‐dusk asymmetric response to enhancement of solar wind dynamics [ Park et al , , ].…”
Section: Summary and Discussionsupporting
confidence: 91%
“…Then, geosynchronous magnetic fields in the prenoon sector should be more sensitive to a change in P sw than in the postnoon sector. Recently, we reported that the normalized sudden commencement amplitudes in the prenoon sector (MLT = 0900–1200) are larger than those in the postnoon sector (MLT = 1200–1500) at geosynchronous orbit [see Park et al , , Figure ]. This indicates that the prenoon sector is more compressed than in the postnoon sector at geosynchronous orbit.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the preference of magnetic local time has been widely observed when the magnetosphere is compressed by a shock. The amplitude of SI (mostly in magnetic B z ) has highest values at local noon equatorial latitudes and decreases from noon toward midnight; no explicit response or even negative response is found in the nightside [ Kokubun , ; Borodkova et al , ; Villante and Piersanti , ; Park et al , ]. Statistical analysis also indicated that the electric field fluctuation is stronger by a factor of 5 to 10 near the noon than in the nightside sector [ Laakso and Schmidt , ].…”
Section: Discussionmentioning
confidence: 99%